Cardio-psycho-metabolic outcomes of bariatric surgery: design and baseline of the WAS trial. Issue 2 (9th February 2022) - Koschker, Ann-Cathrin; Warrings, Bodo; Morbach, Caroline; Seyfried, Florian; Rickert, Nicole; Jung, Pius; Geier, Andreas; Dischinger, Ulrich; Krauthausen, Maike; Herrmann, Martin J; Stier, Christine; Frantz, Stefan; et al.
Abstract : Obesity is a rapidly emerging health problem and an established risk factor for cardiovascular diseases. Bariatric surgery profoundly reduces body weight and mitigates sequelae of obesity. The open, randomized controlled Würzburg Adipositas Studie (WAS) trial compares the effects of Roux-en-Y gastric bypass (RYGB) vs psychotherapy-supported lifestyle modification in morbidly obese patients. The co-primary endpoint addresses 1-year changes in cardiovascular function (peak VO2 during cardiopulmonary exercise testing) and the quality of life (QoL) (Short-Form-36 physical functioning scale). Prior to randomization, all included patients underwent a multimodal anti-obesity treatment for 6–12 months. Thereafter, the patients were randomized and followed through month 12 to collect the primary endpoints. Afterwards, patients in the lifestyle group could opt for surgery, and final visit was scheduled for all patients 24 months after randomization. Sample size calculation suggested to enroll 90 patients in order to arrive at minimally 22 patients per group evaluable for the primary endpoint. Secondary objectives were to quantify changes in body weight, left ventricular hypertrophy, systolic and diastolic function (by echocardiography and cardiac MRI), functional brain MRI, psychometric scales, and endothelial and metabolic function. WAS enrolled 93 patients (72 women, median age 38 years, BMI 47.5 kg/m 2 ) exhibiting a relevantly compromised exercise capacity (median peakVO2 18.3 mL/min/kg) and the QoL (median physical functioning scale 50). WAS is the first randomized controlled trial focusing on the effects of RYGB on cardiovascular function beyond hypertension. In addition, it will provide a wealth of high-quality data on the cerebral, psychiatric, hepatic, and metabolic function in obese patients after RYGB.